Enhancing health and therapeutic potential: innovations in the medicinal and pharmaceutical properties of soy bioactive compounds - Rahman, Ubaidur; Younas, Zohaib; Ahmad, Ilyas; Yousaf, Tayyaba; Latif, Rafia; Rubab, Ume; Hassan, Hira; Shafi, Unsa; Mashwani, Zia-ur-Rehman (Frontiers in Pharmacology, 2024)
An extensive examination of the medical uses of soybean bioactive components is provided by this thorough review. It explores the possible health advantages of isoflavones with phytoestrogenic qualities, like genistein, which may lower the risk of cancer. The review highlights the different roles and possible anticancer activities of phenolic compounds, phytic acid, protease inhibitors, lignans, and saponins, among other bioactive components. It also addresses the benefits of dietary fiber and oligosaccharides derived from soybeans for intestinal health, as well as the impact of soy protein on diabetes, obesity, cancer, and cardiovascular health. Conjugated linoleic acid (CLA) has anticancer and cholesterol-lowering properties; its involvement in promoting metabolic processes is also examined. Pinitol is highlighted in the study as a blood sugar regulator with promise for controlling insulin signaling. In this review, we aim to affirm soybeans' potential as a high-functional, well-being food by examining their recently discovered therapeutic and pharmacological capabilities, rather than to improve upon the previous studies on the reported nutritional advantages of soybeans.